UPPER TRIASSIC AMBER FROM THE DOLOMITES (NORTHERN ITALY).A PALEOCLIMATIC INDICATOR? (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1998)
Amber in Triassic deposits in the Dolomites is demonstrated for the first time. The amber-bearing deposits belong to the middle part of the Dürrenstein Formation, referred to uppermost Julian (Lower Carnian, about 225 My). Chemico-physical features of amber, which occurs as small yellow to reddish droplets, have been determined. Infrared (IR) spectroscopy shows typical bands of fossil resins; the "fingerprint" region of the spectrum presents a unique pattern that cannot be referred to any other known fossil resin. Palynological investigation of amber-bearing layers shows a large prevalence of bisaccates and circumpolles. Particularly, the taeniate bisaccates are frequent (41%) and suggest a correlation with the amber-producing species. Amber production and preservation is possibly related to a humid climatic event.